Observation of Ag Nanoparticles in/on Ag@MIL-100(Fe) Prepared Through Different Procedures - Mahugo, Rubén; Mayoral, Alvaro; Sánchez-Sánchez, Manuel; Diaz, Isabel (Frontiers in Chemistry, 2019)
Loading of active metals, metal clusters and/or metal nanoparticles in Metal Organic Frameworks (MOFs) is an emergent field with applications in sensors, catalysis, medicine and even in the polymeric industry. In the present work, MIL-100(Fe) has been synthesized and reacted with AgNO3 through liquid and incipient wetness, and also through solid-state reaction or solid grinding. The aim of this study is to evaluate whether the MIL-100 would uptake metal particles using a similar principle as that of the ion exchange in zeolites, or else, their inherent humidity would favor the “dissolution” of the metal salt thus yielding very small metal particles. The immobilization of Ag nanoparticles inside the MOF pores was identified by Cs-corrected scanning transmission electron microscopy (Cs-corrected STEM) techniques.